2021
DOI: 10.1016/j.ejor.2019.08.023
|View full text |Cite
|
Sign up to set email alerts
|

A heuristic approach for lactate threshold estimation for training decision-making: An accessible and easy to use solution for recreational runners

Abstract: In this work, a heuristic as operational tool to estimate the lactate threshold and to facilitate its integration into the training process of recreational runners is proposed. To do so, we formalize the principles for the lactate threshold estimation from empirical data and an iterative methodology that enables experience based learning. This strategy arises as a robust and adaptive approach to solve data analysis problems. We compare the results of the heuristic with the most commonly used protocol by making… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This accumulation in lactate reflects the shift from an aerobic to an anaerobic energy production system. Monitoring this shift constitutes an essential parameter to adapt athletes’ training in endurance sports ( Etxegarai et al, 2019 ). In our study, the blood concentration of lactic acid was found to increase significantly during exercise, showing the potential of our method to follow up athletes.…”
Section: Discussionmentioning
confidence: 99%
“…This accumulation in lactate reflects the shift from an aerobic to an anaerobic energy production system. Monitoring this shift constitutes an essential parameter to adapt athletes’ training in endurance sports ( Etxegarai et al, 2019 ). In our study, the blood concentration of lactic acid was found to increase significantly during exercise, showing the potential of our method to follow up athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Etxegarai, Portillo, Irazusta, Arriandiaga, Cabanes (2018) from Spain have tried developing machine learning based LT prediction algorithm and validated with blood lactate LT estimation in recreational runners (Etxegarai et al, 2018). In addition, using heuristic approach, the same research group has developed an equation for recreational runners for LT workload estimation based on running speed reserve and initial running speed on treadmill during a GXT (Etxegarai, Portillo, Irazusta, Koefoed, Kasabov, 2019). These methods if further researched and validated would prove very useful for athletes and active individuals where expertise and facilities for LT estimation are not available.…”
Section: Noninvasive Lt Estimation (Lactate Related)mentioning
confidence: 99%